2017
DOI: 10.1007/s11606-017-4154-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding What Is Most Important to Individuals with Multiple Chronic Conditions: A Qualitative Study of Patients’ Perspectives

Abstract: The domains describe the range and types of personal values multimorbid older adults deem important to well-being and health. Understanding patients' personal values across these domains may be useful for providers when developing, sharing, and following up on care plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 53 publications
2
80
0
1
Order By: Relevance
“…Prior research has suggested that these concerns may receive less attention than medically defined problems during primary care visits. 25,26 In prior studies, identification of psychosocial concerns was by physicians rather than by patients. We had the unique opportunity to examine primary care interactions based on patient-defined visit priorities.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research has suggested that these concerns may receive less attention than medically defined problems during primary care visits. 25,26 In prior studies, identification of psychosocial concerns was by physicians rather than by patients. We had the unique opportunity to examine primary care interactions based on patient-defined visit priorities.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work on methods for eliciting and clarifying values in clinical settings typically focus on eliciting patients' preferences in making individual medical decisions from a set of closed-ended diagnostic or treatment options [44]. Recent work has sought to expand the breadth of values that may be valuable for informing individualized, patient-centered care [27,32]. Domains of values important to people with MCC include those not typically discussed in clinical contexts: activities, possessions, principles, relationships, emotions, and abilities [10,27].…”
Section: Related Work Communication About Patients' Valuesmentioning
confidence: 99%
“…Recent work has sought to expand the breadth of values that may be valuable for informing individualized, patient-centered care [27,32]. Domains of values important to people with MCC include those not typically discussed in clinical contexts: activities, possessions, principles, relationships, emotions, and abilities [10,27].…”
Section: Related Work Communication About Patients' Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors sought to identify what patients with MCC view as most important to their well-being and health. 8 The researchers interviewed 31 older adults (mean age 68.7 years) with diabetes mellitus and at least two other common chronic conditions (depression, osteoarthritis, and coronary artery disease) who received care in a single integrated health care system in Washington state. The authors interviewed patients in their own homes, with optional inclusion of family Published online September 18, 2017 members (18 spouses and 1 adult child participated).…”
mentioning
confidence: 99%